Koefisien Perpindahan Massa Fasa Dispersi Asam Lemak Bebas dari Minyak Sawit Dalam Tangki Berpengaduk - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Mass transfer in the liquid-liquid phase is an important phenomena in the extraction process. Mass transfer coefficient is one of the factors that influence the rate of mass transfer. Nowadays, in the extraction process of free fatty acid from palm oil with methanol, there's no data of dispersion phase mass transfer coefficient. The goal of this research was todetermine and develop correlation of mass transfer coefficient in the dispersion phase on the extraction process of palm oil's free fatty acid with methanol, as the solvent. Therefore, the research was held in two major steps. The first step was held a liquid-liquid extraction in the laboratory, and the second step was develop an empirical correlation for dispersion phase mass transfer coefficient in the term of dimensionless groups. Batch extraction was conducted in an agitated vessel. The variables that is studied in the process include temperature process, solvent to feed weight ratio, and impeller speed. Based on the data that was obtained from the experiment, the correlation equation that can be used to calculate the dispersion phase mass transfer coefficient was expressed by Sherwood number and could be correlated with turbine Reynolds number, Schmidt number, (dp/dT) and (L/S), and correlation is: Sh= 9,83x104 Re0.462 SC" (dp/dT)"Â°8 (L/S)"87 If the correlation above is used to calculate the mass transfer coefficient, the averege deviation is 9,8%. These dimensionless groups are developed in the range of 3169 to 11750, 6321 to 9897, 0,0007 to 0,0013, and 0,333 to 1 in the Reynolds number, Schmidt number, (dp/dT), and (L/S), respectively. Key words : dispersion phase, extraction, mass transfer coefficient